Analisis Tata Kelola Penyelenggaraan Kelas Internasional terhadap Kepuasan Mahasiswa di Universitas Brawijaya - Sylviani, Sri Mulyani (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
The purpose of the study was to determine the level of satisfaction of international class students, the governance of the implementation of international classes at Brawijaya University. Method This research is quantitative using a survey approach with an associative approach. This study uses a population of all students in the International class of Universitas Brawijaya, which is 477 people from the class of 2017, 2018, 2019, 2020, and 2021. The sample was taken using the slovin formula, the sampling technique used stratified random sampling so that a sample of 218 was obtained. person. The instrument in the study was valid and reliable. The data analysis method used multiple linear regression analysis. The results of the study prove that transparency (X1), accountability (X2), responsibility (X3), independence (X4), fairness (X5), quality assurance and relevance (X6), effectiveness and efficiency (X7), non-profit (X8) significant effect on student satisfaction (Y). Research can be a reference for the management of Universitas Brawijaya in improving the quality of education services for international class students.